PCR-Based Detection and Genotyping of Helicobacter pylori in Endoscopic Biopsy Samples from Brazilian Patients - Silvia M. Ferreira Menoni; Sandra Helena Alves Bonon; José Murilo Robilota Zeitune; Sandra Cecília Botelho Costa (Gastroenterology Research and Practice)
Helicobacter pylori (H. pylori) is considered the second most prevalent infection in man. A precise diagnosis is important for treating patients with the indicative gastrointestinal symptoms. The present study analyzes the effectiveness of a molecular biology method (PCR) comparing the results obtained with the histology and with the rapid urease tests. PCR was used in the detection and genotyping of the H. pylori urease-C gene and the patterns which were obtained from the patients studied. 141 biopsy samples from 131 patients were evaluated. 59 paraffin biopsies samples were positive for H. pylori according to the histological examination. Of those, 59/12 (20.3%) were amplified using PCR. Of the 82 samples from the fresh biopsies, 64 were positive for H. pylori according to the rapid urease test (78%); there was an agreement of 100% with PCR. Sixty positive H. pylori samples were genotyped (58 samples of fresh biopsies and 2 samples of paraffin biopsies) using two restriction enzymes. The patterns observed were analyzed with the computational program BIO 1D; 11 patterns with the enzyme HhaI and 12 patterns with the enzyme MboI were found. However, it was not possible to find a statistically significant correlation between the specific genotypes and digestive pathologies. Accordingly, future research should be performed to confirm a statistically significant relationship between genotyping and gastrointestinal symptoms.